The Role of Supreme Audit Institution in Supporting Sustainable Development Goals Implementation: A study in Indonesia - Togatorop, Wahyu Ida Arinta; Setyono, Jawoto Sih (The Indonesian Journal of Planning and Development, 2021)
SDGs 2030 is a guide for countries in carrying out development to reduce poverty, protect the planet, and ensure the prosperity of all people in the world. Achieving the 17 SDGs is challenging and complex since each goal is related to other goals. SDGs implementation requires the involvement of multi-stakeholders. One of the parties that play a critical role in SDGs implementation is the Supreme Audit Institution (SAI). Under the auspices of the INTOSAI, SAIs agree to support the government's efforts to implement and achieve SDGs 2030, including the Indonesian Supreme Audit Board Republic of Indonesia (BPK). This study aims to provide a deeper understanding of the role of SAI in SDGs implementation and how BPK supports the Indonesian government in achieving the SDGs 2030 Agenda. The research uses qualitative method which is based on secondary data such as journals, articles, and institutional reports collected from the online library. The author chooses descriptive analysis as the data analysis method to describe the information collected in the documents and previous articles. In order to gain more data about BPK's Audit from 2016-2020, the researcher utilized the information obtained from the Semester Examination Results Summary published by BPK. Research shows that SAI has a significant contribution to SDGs implementation by conducting audits, cooperation and collaboration with other parties, and increasing the human resources in SDGs audit. The study of BPK in supporting the SDGs implementation in Indonesia shows that BPK is keep enhancing its role by doing audits related to SDGs, developing integration with other SAI’s association, and improving the auditor’s capacity in carrying out the SDGs audit in the future.